Effects of Nonpharmacological Interventions on Disruptive Vocalisation in Nursing Home Patients With Dementia—A Systematic Review - Bilal Ahmed, Saad; Obieta, Alfredo; Santos, Tamsin; Ahmad, Saara; Elliot Ibrahim, Joseph (Frontiers in Rehabilitation Sciences, 2022)
Background: Vocally disruptive behaviour is a common and difficult to treat condition in older residents with dementia. The aim of this systematic review is to evaluate the efficacy of non-pharmacological interventions in its management in persons with dementia residing in a nursing home. Methodology: A systematic search was conducted using Ovid MEDLINE, CINAHL and Cochrane databases, and reference lists from relevant publications on various non-pharmacological approaches to manage vocally disruptive behaviour in nursing home residents. The method of appraisal was through the National Institutes of Health scoring for the Quality Assessment of Controlled Intervention Studies. Inclusion criteria included residents of nursing homes over the age of 65 with dementia and disruptive vocalisation. Only randomised controlled trials published in English were included. Results: A total of 5606 articles were identified, covering 501 trials, of which 23were selected. There were fourteen studies observed to have an impact of clinical and statistical significance with interventions including: (i) a multidimensional approach with different non-pharmacological interventions, (ii) multisensory stimulation, (iii) staff education and training (iv) personalised bathing and (v) pain recognition and appropriate management. Seven studies demonstrated no observable effect while two showed worsening in vocally disruptive behaviour. Conclusions: Many aspects of vocally disruptive behaviour management are poorly understood. Limited empirical evidence supports the use of several non-pharmacological interventions to reduce it. There is more robust evidence to support the use of a tailored approach to management over the universal approach.